OPTIMASI PROSES EKSTRAKSI MINYAK DAN RESIN NYAMPUNG DENGAN PELARUT BINER MENGGUNAKAN RESPONSE SURFACE METHOD - Ika Amalia Kartika; Ikbal Fataya; Muhamad Yunus; Nancy Dewi Yuliana (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Calophyllum seeds are potential to be used as raw material for vegetable oil production due to their high oil content. In addition, Calophyllum seeds contain resin consisting of beneficial phenolic compounds for health. The objective of this research was to optimize the oil and resin extraction from Calophyllum seeds on a pilot scale using binary solvent. The analyses of temperature, extraction time and stirring speed effects on the oil and resin yields were carried out using the central composite design, and the variables were optimized using the response surface method. The result of oil yield optimization showed that the best model was the quadratic model. The optimum oil yield (59%) was obtained at temperature of 49.4 oC, extraction time of 5.3 h, and stirring speed of 385 rpm. The result of resin yield optimization showed that the best model was the mean model with average value of 15% for all extraction conditions tested. Model validation at this extraction condition resulted actual oil (60%) and resin (13%) yields conformed passably to their prediction. In addition, the oil and resin obtained from this model validation had good characteristics, and matched the predicted results. Keywords: binary extraction, Calophyllum, oil, optimization, resin, response surface method